Edukasi teknologi hidroponik untuk pemberdayaan lahan pekarangan - Ismail Ismail; Agus Syam (Universitas Negeri Makassar, 2019)
The acceleration of diversification of food consumption based on local resources has become a government policy. One form of the implementation of the policy is the optimization of the use of the yard. To optimize the function of the yard as a source of vegetable food, training in hydroponic technology education activities has been conducted with community partners in the village of Tunikamaseang, Maros Regency. The Community Partnership Program is carried out with the aim of increasing: 1) hydroponic system vegetable farming techniques and skills, 2) increasing family food security. The method used is the reflection, demonstration and practice of hydroponic system cultivation, with the Participatory Rural Appraisal approach. The result of devotion achieved is an increase in partner's knowledge and skills in the cultivation of the hydroponic system. The output of this activity is the vegetable cultivation model of the hydroponic system.